Recurrent TTN metatranscript‐only c.39974–11T>G splice variant associated with autosomal recessive arthrogryposis multiplex congenita and myopathy. Issue 2 (3rd December 2019) - Bryen, Samantha J.; Ewans, Lisa J.; Pinner, Jason; MacLennan, Suzanna C.; Donkervoort, Sandra; Castro, Diana; Töpf, Ana; O'Grady, Gina; Cummings, Beryl; Chao, Katherine R.; Weisburd, Ben; Francioli, Laurent; et al.
Abstract: We present eight families with arthrogryposis multiplex congenita and myopathy bearing a TTN intron 213 extended splice‐site variant (NM_001267550.1:c.39974‐11T>G), inherited in trans with a second pathogenic TTN variant. Muscle‐derived RNA studies of three individuals confirmed mis‐splicing induced by the c.39974‐11T>G variant; in‐frame exon 214 skipping or use of a cryptic 3′ splice‐site effecting a frameshift. Confounding interpretation of pathogenicity is the absence of exons 213‐217 within the described skeletal muscle TTN N2A isoform. However, RNA‐sequencing from 365 adult human gastrocnemius samples revealed that 56% specimens predominantly include exons 213‐217 in TTN transcripts (inclusion rate ≥66%). Further, RNA‐sequencing of five fetal muscle samples confirmed that 4/5 specimens predominantly include exons 213‐217 (fifth sample inclusion rate 57%). Contractures improved significantly with age for four individuals, which may be linked to decreased expression of pathogenic fetal transcripts. Our study extends emerging evidence supporting a vital developmental role for TTN isoforms containing metatranscript‐only exons.